Association Between Elevated Mean Arterial Blood Pressure and Neurologic Outcome After Resuscitation From Cardiac Arrest: Results From a Multicenter Prospective Cohort Study*. Issue 1 (January 2019) - Roberts, Brian W.; Kilgannon, J. Hope; Hunter, Benton R.; Puskarich, Michael A.; Shea, Lisa; Donnino, Michael; Jones, Christopher; Fuller, Brian M.; Kline, Jeffrey A.; Jones, Alan E.; Shapiro, Nathan I.; Abella, Benjamin S.; et al.
Abstract : Objectives: Laboratory studies suggest elevated blood pressure after resuscitation from cardiac arrest may be protective; however, clinical data are limited. We sought to test the hypothesis that elevated postresuscitation mean arterial blood pressure is associated with neurologic outcome. Design: Preplanned analysis of a prospective cohort study. Setting: Six academic hospitals in the United States. Patients: Adult, nontraumatic cardiac arrest patients treated with targeted temperature management after return of spontaneous circulation. Interventions: Mean arterial blood pressure was measured noninvasively after return of spontaneous circulation and every hour during the initial 6 hours after return of spontaneous circulation. Measures and Main Results: We calculated the mean arterial blood pressure and a priori dichotomized subjects into two groups: mean arterial blood pressure 70–90 and greater than 90 mm Hg. The primary outcome was good neurologic function, defined as a modified Rankin Scale less than or equal to 3. The modified Rankin Scale was prospectively determined at hospital discharge. Of the 269 patients included, 159 (59%) had a mean arterial blood pressure greater than 90 mm Hg. Good neurologic function at hospital discharge occurred in 30% of patients in the entire cohort and was significantly higher in patients with a mean arterial blood pressure greater than 90 mm Hg (42%) as compared with mean arterial blood pressure 70–90 mm Hg (15%) (absolute risk difference, 27%; 95% CI, 17–37%). In a multivariable Poisson regression model adjusting for potential confounders, mean arterial blood pressure greater than 90 mm Hg was associated with good neurologic function (adjusted relative risk, 2.46; 95% CI; 2.09–2.88). Over ascending ranges of mean arterial blood pressure, there was a dose-response increase in probability of good neurologic outcome, with mean arterial blood pressure greater than 110 mm Hg having the strongest association (adjusted relative risk, 2.97; 95% CI, 1.86–4.76). Conclusions: Elevated blood pressure during the initial 6 hours after resuscitation from cardiac arrest was independently associated with good neurologic function at hospital discharge. Further investigation is warranted to determine if targeting an elevated mean arterial blood pressure would improve neurologic outcome after cardiac arrest. Abstract : Supplemental Digital Content is available in the text.